--and justice for all [videorecording (DVD)] - Jewison, Norman, 1926-; Pacino, Al, 1940-; Warden, Jack; Strasberg, Lee; Forsythe, John, 1918-2010 (Image Entertainment, 2010)
When a corrupt judge is charged with rape, Arthur Kirkland must defend him. Kirkland has had problems with the judge in the past, including one incident when the judge wrongly sentenced his client, Jeff McCullaugh, because of a technicality. Kirkland faces a moral and legal dilemma, especially difficult because the judge admits he is guilty.